The Effectiveness Test of Essential Oils to Control Fruit Fly (Bactrocera sp.) on Crystal Guava (Psidium guajava L.) - Helmawan, Finda Luthfia; Mursiani, Sri; Septia, Erfan Dani (Journal of Tropical Crop Science and Technology, 2023)
This Crystal Guava was introduced in Indonesia in 1991 by the Taiwan Technical Mission. Various attempts have been made to achieve maximum productivity results, but these efforts have not been fully successful due to constraints such as pest attacks. Pests that attack crystal guava fruit are fruit fly pests. Fruit fly pests are pests that damage plants, especially types of horticultural crops, especially fruit and vegetable plants. Fruit fly attacks in Indonesia reach 50% and when the fruit fly population is high, the attack intensity can reach 100%. The purpose of this study was to find out the types of plant extracts that are effective and effective in attracting fruit flies in pest control, to find out the optimal concentrations to attract fruit flies in pest control in guava crystals and to find out the best time to apply extracts to attract flies. fruit in pest control on crystal guava plants. The data obtained from this study were presented in a factorial randomized block design (RBD) with 3 factors. This study consisted of 27 treatment combinations and 1 control with 3 repetitions and each treatment in one repetition there were 5 samples. Observational data were analyzed using Analysis of Variance (ANOVA) and interpretation of the data was carried out by further testing using the Honest Significant Difference (HSD) test at 5% level and orthogonal contrast test.